Use of point of view cameras for welfare management in extensive grazing systems - Sales-Baptista, Elvira (2020)
Grazing patterns can be a major indicator for welfare assessment in extensive systems. The aim of this study was to test animal-borne video as a method to evaluate sheep grazing behavior. To test the changes in grazing duration, grazing frequency and grazing rate, we used wide angle cameras (Go-Pro and infra-red night vision) to access diurnal and nocturnal grazing activities of ewes in a native sward, during two weeks in late spring, the season with greatest changes in weather and vegetative growth. Three ewes were chosen from a flock of 15 animals for focal observation. The foraging behaviour of the entire flock were recorded by scan sampling with a 10-minute interval. Grazing bout duration increased significantly between the first (44.6 ± 41.4 s) and the second week (94.0 ± 57.0 s) (F = 10.295, P<0.05). Conversely, grazing bout duration differed among grazing hours (F = 4.523, P<0.05), with a peak for the dusk grazing period (128.1 ± 88.8 s). Nocturnal grazing did not differ significantly for any of the grazing parameters, although a general trend for longer grazing duration through time was observed. Sheep spend the hot part of the day lying in shade under trees and use more than one tree as resting areas. A significant correlation was shown to exist between the grazing behaviour estimated from focal sampling with video cameras and the scan sampling (r2=0.83). We concluded that animal-borne video cameras are a method appropriate for assessing sheep variations of grazing behaviour structure allowing to understand differences of adaptive grazing patterns that can be useful for welfare management in extensive systems.